2013
DOI: 10.9734/ijbcrr/2013/3859
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-diabetic and Liver Enzymes Activity of Aqueous Extracts of Moringa oleifera and Bridelia ferruginea Leaves in Alloxan Induced Diabetic Albino Rats

Abstract: Aims: To evaluate anti-diabetic and liver enzymes activities of aqueous extracts of Moringa oleifera and Bridelia ferruginea leaves in alloxan induced diabetic albino rats. Study design: Diabetes was induced in three groups of rats, one group was not treated while two groups were treated orally with M. oleifera and B. ferruginea extracts at 200, 400 and 800 mg/kg body weight of rats twice for 1 week respectively. One group was not induced and received distilled water only. The anti-diabetic and liver enzymes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
49
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 23 publications
8
49
1
Order By: Relevance
“…But these results was disagreement with those obtained by Shank et al, (2013) who reported that MS medium supplemented with 0.5mg/l of 2,4-D was the most effective medium for callus induction of M. oleifera with 100% of callus induction from week-3 after culturing of shoot, Figure 1 showing the callus mass of M. oleifera which grown on MS medium after two subcultures. Results in table 3 described the changes in the weight of animals based on varying extract doses during the 15 days of treatment and showed that the body weight of mice significantly increased in the positive control group and those treated with 20, 40 and 80% of M. oleifera leaves or callus extracts compared with negative control which was significantly decreased with increasing days of treatment, these results was agreement with those obtained by Aja et al, (2013) who reported a significant (P<0.05) reductions in the mean body weight of rats in diabetic control compared to positive group while rats in treated groups showed significant (P<0.05) increase in their mean body weight compared to diabetic control group in work done earlier on antidiabetic effect of aqueous extract of Moringa oleifera and Bridelia ferruginea leaves in alloxan-induced diabetic albino rats. Data displayed in table 4 show that administration of Moringa oleifera ethanol extracts of either leaves or callus tissues in alloxan induced diabetic albino mice at various doses of 20, 40 and 80% reduce the blood glucose level in the treated mice significantly compared to the negative control.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…But these results was disagreement with those obtained by Shank et al, (2013) who reported that MS medium supplemented with 0.5mg/l of 2,4-D was the most effective medium for callus induction of M. oleifera with 100% of callus induction from week-3 after culturing of shoot, Figure 1 showing the callus mass of M. oleifera which grown on MS medium after two subcultures. Results in table 3 described the changes in the weight of animals based on varying extract doses during the 15 days of treatment and showed that the body weight of mice significantly increased in the positive control group and those treated with 20, 40 and 80% of M. oleifera leaves or callus extracts compared with negative control which was significantly decreased with increasing days of treatment, these results was agreement with those obtained by Aja et al, (2013) who reported a significant (P<0.05) reductions in the mean body weight of rats in diabetic control compared to positive group while rats in treated groups showed significant (P<0.05) increase in their mean body weight compared to diabetic control group in work done earlier on antidiabetic effect of aqueous extract of Moringa oleifera and Bridelia ferruginea leaves in alloxan-induced diabetic albino rats. Data displayed in table 4 show that administration of Moringa oleifera ethanol extracts of either leaves or callus tissues in alloxan induced diabetic albino mice at various doses of 20, 40 and 80% reduce the blood glucose level in the treated mice significantly compared to the negative control.…”
Section: Resultssupporting
confidence: 81%
“…Data displayed in table 4 show that administration of Moringa oleifera ethanol extracts of either leaves or callus tissues in alloxan induced diabetic albino mice at various doses of 20, 40 and 80% reduce the blood glucose level in the treated mice significantly compared to the negative control. But callus extract was more effective than those of leave extracts in returning the animal's body weight and blood glucose level to the normal in comparison to negative control, using plant extracts for diabetic treatment appeared to be generally safe due to the presence of bioactive compounds especially in those of medicinal plants which have hypoglycemic effects through reduction insulin resistant, induction the releasing and inhibition glucagon secretion, slowing down the digestion and absorption of carbohydrates or by decreasing hepatic glucose production (Aja et al,,2015). M. oleifera as a medicinal plant contains flavonoids, stilbeans, terpenoids, glycoside and alkaloids as its bioactive compounds as mentioned by Gupta and Misra, (2006) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both plants were found to show a significant reduction in plasma glucose level at an oral extract dose of 200, 400 and 800mg/kg body weight of diabetic rats treated twice daily for seven days. The outcome of study suggests that both extracts can be used in ethno-medicine for the management of diabetes mellitus [39]. In another study, the effect of aqueous leaf extract of Moringa oleifera on plasma glucose level, total cholesterol, triglyceride, high density lipoprotein and low-density lipoprotein in male albino rats revealed that aqueous extract of Moringa oleifera reduces the plasma lipid imbalance associated with diabetes mellitus.…”
Section: International Journal Of Pharmacology Phytochemistry and Etmentioning
confidence: 96%
“…Diabetes mellitus is a chronic disease occurs due to either an autoimmune disorder or insulin resistance. Autoimmune disorder (type I diabetes) appears as a result of β-cells failure to secrete insulin (Aja et al, 2015). Interrupted signal transduction pathway occurs as a result of defects of insulin receptors which is routinely called type II diabetes leading to elevated blood glucose level (hyperglycemia) (Bamidele et al, 2014).…”
Section: Introductionmentioning
confidence: 99%